Capital income shares and income inequality in 16 EU member countries - Eva Schlenker; Kai D. Schmid (Institut für Angewandte Wirtschaftsforschung (IAW), 2014)
In this paper, we estimate the effect of changes in capital income shares on inequality of gross household income. Using EU-SILC data covering 16 EU countries from 2005 to 2011 we find that the level of capital income shares is positively associated with the concentration of gross household income. Moreover, we show that the transmission of a shift in capital income shares into the personal distribution of income depends on the concentration of capital income in an economy. At the mean of the distribution of capital income a 1 percentage point increase of the capital share is associated with a 0.8 percentage point increase of the Gini coefficient of gross household income. Our findings imply that in many industrialized countries income inequality has by no means evolved independently from the observed structural shift in factor income towards a higher capital income share over the last decades.
Keywords: D31; D33; E6; E25; 330; Factor Income Shares; Income Inequality; EU-SILC; Fixed Effects